Uganda : 2021 Article IV Consultation and First Review under the Extended Credit Facility Arrangement and Requests for Modifications of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Uganda. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
The authorities have reacted to the COVID-19 crisis in an appropriate manner, including through increased spending on health and a rollout of the vaccination program. Nevertheless, the deterioration of socio-economic indicators during the pandemic could create scars that would significantly lower growth if left unaddressed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Uganda